PROTECTION OF THE DISABLED IN THE WORK ENVIRONMENT - Jovanović, Predrag (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The disabled enjoy special protection at work (in the work environment). The importance of this protection essentially determines the status of the disabled in the society, because it is connected with the work of the disabled with which get the means of life, but they are also brought into an equal position with other persons that do not have disability and whose working abilities are not reduced. There is a lot of vagueness in terms of terminological and meaning determination of the concept of disability, both in the international and the domestic law. We tried to elaborate the issue of disability in the paper firstly in the terminological and meaning sense and then to present international legal and domestic platform of their protection at work connected with the work, too (the work environment). Special emphasis was put on the concept of the disabled worker and their equal protection, with a critic review on the existing solutions in the effective law. инвалида, а затим прикажемо међународно-праву и домаћу правну платформу њихове заштите на раду и у вези са радом (у радној средини). Посебан акценат је стављен на појам инвалида рада и њихове радноправне заштите, уз критички осврт на постојећа решења у важећем праву.